2021
DOI: 10.9734/cjast/2021/v40i731322
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Micro-nutrition of Vegetable Crops - A Critical Review

Abstract: Foliar Micro-nutrition is the application of micronutrients to plants by spraying directly onto their leaves. Although it is not economical to spray macronutrients and micronutrients through foliar spraying, researchers prefer soil application for macronutrients and foliar applications of micronutrients. Several researches have demonstrated that the method which is used to deliver the required micronutrient in appropriate concentration to improve nutrient status along with increased yield and quality potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
3
0
4
Order By: Relevance
“…The largest amount of tissue permeability is favoured in warm, humid and tranquil environments. These conditions most frequently seen in late-night hours and often in early morning hours" [27]. "Since plant tissue does not immediately absorb all nutritional materials, rainfall may reduce the efficiency of foliar treatment within 24 to 48 hours of administration.…”
Section: Factors Affecting the Efficiency Of Foliar Nutritionmentioning
confidence: 99%
“…The largest amount of tissue permeability is favoured in warm, humid and tranquil environments. These conditions most frequently seen in late-night hours and often in early morning hours" [27]. "Since plant tissue does not immediately absorb all nutritional materials, rainfall may reduce the efficiency of foliar treatment within 24 to 48 hours of administration.…”
Section: Factors Affecting the Efficiency Of Foliar Nutritionmentioning
confidence: 99%
“…Micronutrients are elements that are required for plant growth in minute concentrations. Despite being required in fewer quantities, micronutrients have the same functional importance as macronutrients and play critical roles in plant growth [1]. These elements include, Zinc (Zn), Iron (Fe), Copper (Cu), and Manganese (Mn) amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…Micronutrients in soil exist in various forms, including water-soluble, exchangeable, complex and chelated forms, as well as in the structure of primary and secondary minerals [4]. Numerous studies have demonstrated that the availability of micronutrients in the rhizosphere relies on soil pH, organic matter, clay content, and other physical, chemical, and biological factors [1]. According to [5], Fe and Mn are prevalent in silicate minerals including biotite and hornblende.…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, se ha documentado que niveles altos y excesivos de Ca en el suelo pueden disminuir la absorción de micronutrientes por las plantas, limitando significativamente la producción de los cultivos (Prasad et al, 2016;Abou et al, 2021). Por lo anterior, la nutrición foliar puede complementar a la fertilización edáfica, especialmente con micronutrientes, que por lo general su absorción a través de las raíces es limitada por varios factores limitantes del suelo, más aún en sistemas de secano, donde la baja humedad del suelo limita la absorción eficiente de nutrientes (Subhani et al, 2012;Shiferaw, 2017;Niu et al, 2020;Zahed et al, 2021). En relación con lo descrito, estudios realizados por Potarzyck & Grzebisz (2009) y Liu et al (2020) concluyeron que aplicaciones foliares de Zn incrementaron hasta en 18% y 17% el rendimiento de grano del maíz en Polonia y China, respectivamente.…”
Section: Introductionunclassified